2021
DOI: 10.1002/osp4.533
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of addressing obesity in people with poorly controlled asthma

Abstract: Objective: There is a high prevalence of obesity in people with asthma, and obesity is associated with poorly controlled asthma. Significant weight loss might improve asthma control: the purpose of this study was to investigate patient characteristics and factors that might affect implementation of a weight loss and/or roflumilast intervention, to target both obesity and asthma. Methods:A cross-sectional study of people with obesity and poorly controlled asthma performed at 13 sites across the United States.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…88 However, exercise interventions might be challenging for people suffering with asthma and obesity. Our own group has found that patients with obesity and asthma, which frequently affects minority populations, were associated with marked impairments in quality of life related to physical health, and low levels of physical activity, 89 suggesting that weight loss interventions that include significant exercise component will likely need to be tailored for people with marked impairments in physical health. 90 Short of weight loss, focusing on dietary quality may be another strategy to improve asthma control.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…88 However, exercise interventions might be challenging for people suffering with asthma and obesity. Our own group has found that patients with obesity and asthma, which frequently affects minority populations, were associated with marked impairments in quality of life related to physical health, and low levels of physical activity, 89 suggesting that weight loss interventions that include significant exercise component will likely need to be tailored for people with marked impairments in physical health. 90 Short of weight loss, focusing on dietary quality may be another strategy to improve asthma control.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Therefore, an improved adherence to usual treatment and/or a better handling of aerosol devices by the patient might have led to a better asthma control and quality of life [ 41 ]. Second, we have also to consider non-pharmacological factors such as an engagement of the patient toward a better nutrition or regular physical activity [ 42 , 43 ] as it is generally advised by the health care professionals working in our asthma clinic. Our finding is supported by the demonstration that providing patient with information about the disease, particularly by increasing patients’ knowledge of how to treat their symptoms, may improve asthma control and quality of life [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Late-onset non-allergic asthma developing as a complication of obesity (4)(5)(6)(7). The latter primarily affects women, exhibits low inflammatory markers, does not feature eosinophilia, and often shows improvement in airway symptoms with weight loss.…”
Section: Introductionmentioning
confidence: 99%